Effect of elevated temperatures on concrete made with recycled concrete aggregates - An overview. (December 2021) - Fernandes, Bruno; Carré, Hélène; Mindeguia, Jean-Christophe; Perlot, Céline; La Borderie, Christian
Abstract: In the last decades, the use of recycled concrete aggregates (RCA) has proven to be a good solution for making sustainable concrete. Concretes made with RCA show reasonable performance at ambient temperature and has already been used in different real applications. The broader application of concrete with RCA, however, depends on a better understanding of its fire behaviour, a critical factor for building structures. Within this framework, this paper presents a review of previous works on the behaviour of concrete made with RCA at high temperatures. Experimental works on the mechanical and thermal properties are compiled and discussed, to identify the temperature dependency of these properties and the influence of different materials and test parameters. Studies dealing with spalling and the fire behaviour of medium and full-scale concrete elements are also presented. Lastly, the microstructure alterations of heated concrete made with RCA are addressed. The results under review show that the properties of concrete with RCA are affected by the increase of temperature. The influence of the RCA, however, is not well defined. The different theories behind the high temperature behaviour of concrete with RCA are discussed and presented. Lastly, comments are made on the current knowledge gaps and future research needs. Highlights: Behaviour of concrete made with RCA at high temperatures is reviewed. Mechanical, thermal and microstructural properties are discussed. Medium, full-scale and spalling studies are reported. The effect of replacement rate and comparisons with concrete with NA are addressed. Future challenges and research needs are discussed.